Hispanic or Latino Student Success in Online Schools - Michael Corry (Athabasca University Press, 2016)
The purpose of this study is to examine graduation and dropout rates for Hispanic or Latino K–12 students enrolled in fully online and blended public school settings in Arizona.  The independent variables of school type (charter vs. non-charter) and delivery method (fully online vs. blended) were examined using multivariate and univariate methods on the dependent variable’s graduation and dropout rates for Hispanic or Latino students.  The results of this research study found a statistically significant difference when using multivariate analysis to examine school type (charter vs. non-charter) and delivery method (fully online vs. blended) on graduation and dropout rates. This finding warranted further univariate examination which found a statistically significant difference when examining delivery method on dropout rates.  A comparison of mean dropout rates shows that Hispanic or Latino students involved in K–12 online learning in Arizona are less likely to drop out of school if they are in a fully online learning environment versus a blended learning environment.  Students, parents, teachers, administrators, instructional designers, and policy makers can all use this and related research to form a basis upon which sound decisions can be grounded.  The end result will be increased success for Hispanic or Latino online K–12 students not only in Arizona schools, but in many other important areas of life.